EFEKTIVITAS PELAYANAN KESEHATAN PADA BAGIAN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH (RSUD) I LAGALIGO WOTU - Desak Nyoman Suartini (Stikes Graha Edukasi Makassar, 2019)
The purpose of the study: to find out the description of the effectiveness of health services in the inpatient section at the Lagaligo Regional General Hospital I. Method: The type of research used was an observational study with a descriptive design, where the aim of this study was to determine the effectiveness of health services in the inpatient section at Andi Djemma Regional General Hospital in North Luwu based on aspects of disciplinary staff, officer ethics, and number of officers. Data collection is done by direct interview using a questionnaire which is then processed using computer assistance SPSS for windows program and presented in the form of a frequency distribution table. Results: The effectiveness of services in the inpatient room of Lagaligo I General Hospital in terms of disciplinary aspects of staff in the adequate category is 49 (63.6%), where officers are always on time, conducting checks and supervision, officers are easily contacted when needed by patients. Discussion: Increasing the effectiveness of health services in hospitals is needed along with the increasing demand (demand) of the community for quality services. Conclusion: Based on the results of the study, the results showed that service effectiveness in terms of disciplinary aspects was more dominant in the adequate category, service effectiveness in terms of officer ethics was more dominant in the adequate category, service effectiveness in terms of the number of officers was more dominant in the category. Suggestion: It is suggested that the managerial party in this case the hospital as the policy maker is expected to pay more attention to the services provided, even though discipline, ethics and the number of officers are more dominant in the sufficient category, the services provided need to be maintained and improved again. Hospitals should facilitate and provide opportunities for increasing staff resources by increasing the education level of staff and regularly conducting training in order to support more effective services